1976
DOI: 10.1086/208662
|View full text |Cite
|
Sign up to set email alerts
|

It's the Thought that Counts: A Signed Digraph Analysis of Gift-Giving

Abstract: This article presents and tests a model of gift selection based on cognitive consistency theories. The model, which is supported by the data presented, offers a means for predicting the conditions under which giver tastes or recipient tastes dominate gift selection, and for predicting the amount of satisfaction which the gift brings the giver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
160
0
18

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(180 citation statements)
references
References 23 publications
2
160
0
18
Order By: Relevance
“…Theorists have posited that gifts play an important role in the context of social relationships because gifts act as markers of similarity in tastes and interests between relationship partners, signaling partner compatibility (Belk, 1976(Belk, , 1979Belk & Coon, 1993;Larsen & Watson, 2001;Schwartz, 1967;Sherry, 1983). Consistent with this idea, Davis, Hoch, and Ragsdale (1986) found that people's predictions about which products their spouse would like were driven primarily by their own product preferences.…”
mentioning
confidence: 99%
“…Theorists have posited that gifts play an important role in the context of social relationships because gifts act as markers of similarity in tastes and interests between relationship partners, signaling partner compatibility (Belk, 1976(Belk, , 1979Belk & Coon, 1993;Larsen & Watson, 2001;Schwartz, 1967;Sherry, 1983). Consistent with this idea, Davis, Hoch, and Ragsdale (1986) found that people's predictions about which products their spouse would like were driven primarily by their own product preferences.…”
mentioning
confidence: 99%
“…11 Chevalier, et al (2003) also find that changes in wholesale prices at this chain are small in absolute as well as in relative terms. 12 See, for example, Belk (1976), Cheal (1987), and Otnes, et al (1993). 13 The costs of price adjustment theory, which, as Muller, et al (2002) have argued, lead to the holiday price rigidity for both branded and private label products, is obviously an exception.…”
mentioning
confidence: 99%
“…Thus, gift giving, as well as exchanging, is sharing, and it results in ownership transfer. Likewise, the act of giving, called gift giving, is a way of transferring ownership by sharing (Belk, 1976;Sherry Jr., 1983). Therefore, we have identified different types of sharing.…”
Section: Exploring the Boundaries Of Sharing Economy And Collaborativmentioning
confidence: 99%